1993
DOI: 10.1111/j.1600-0609.1993.tb00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating megakaryocytes: Delivery of large numbers of intact, mature megakaryocytes to the lungs

Abstract: To determine the locus of platelet production, we sought to determine if sufficient megakaryocytes reach the lungs in a state that could produce platelets. Elutriation was used to isolate megakaryocytes from blood reaching and leaving the lungs of 20 patients undergoing routine cardiac catheterizations. A mean of 5.0 intact megakaryocytes/ml were found in pulmonary artery blood, compared to only 0.5 megakaryocytes/ml, with partial cytoplasmic content, in aortic samples. The megakaryocytes in central venous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 51 publications
2
62
0
2
Order By: Relevance
“…The romiplostim-induced increase in BM and spleen MK numbers was accompanied by an increase in MK transmigration as shown by the higher number of MK nuclei emboli counted in pulmonary vasculature ( Figure 5). The presence of MKs or MK nuclei in the lungs has long been reported 16,23,24 and is particularly increased in cases of reactive thrombopoiesis or after TPO treatment 16 in agreement with the present observations. In addition, infusion of mature MKs into mice mostly localized to the pulmonary vasculature where they release platelets.…”
Section: Org Fromsupporting
confidence: 92%
“…The romiplostim-induced increase in BM and spleen MK numbers was accompanied by an increase in MK transmigration as shown by the higher number of MK nuclei emboli counted in pulmonary vasculature ( Figure 5). The presence of MKs or MK nuclei in the lungs has long been reported 16,23,24 and is particularly increased in cases of reactive thrombopoiesis or after TPO treatment 16 in agreement with the present observations. In addition, infusion of mature MKs into mice mostly localized to the pulmonary vasculature where they release platelets.…”
Section: Org Fromsupporting
confidence: 92%
“…[7][8][9] More recently, using intravital microscopy to visualize platelet generation in mice, Junt et al 10 have provided evidence that MKs extend voluminous processes into the lumen of sinusoids, which are sheared off by the flowing blood and thereby produce proplatelets that subsequently fragment into individual platelets. 2,[11][12][13] Although the DMS has been well characterized at the end stages of MK maturation, little is known about the biogenesis of this unique membrane system during the initial stages of MK development. Various subcellular origins have been proposed as a source of DMS biogenesis: (1) the MK plasma membrane (PM), (2) specializations of the endoplasmic reticulum (ER) or the Golgi apparatus, and (3) de novo membrane formation.…”
Section: Introductionmentioning
confidence: 99%
“…28 Indeed, the large cytoplasmic fragments and the isolated platelet-sized fragments that we observed in real time to form on the coverslip during the flow assay resembled those seen downstream of the pulmonary circulation in vivo. 33 In our conditions, high shear rates were essential to proplatelet and platelet formation during an exposure time of 20 minutes. In contrast, no proplatelet or platelet was generated in static conditions during this short period.…”
mentioning
confidence: 99%
“…21 Thus MK fragmentation leading to platelets may occur intravascularly and be finely regulated depending on the release of VWF from Weibel-Palade bodies, as well as on the VWF content of endothelial cells that is known to be heterogeneous along the vascular bed, and particularly high in the pulmonary artery. 44,45 Indeed, there is evidence that platelet counts are higher in pulmonary venous samples than in pulmonary arterial blood, 28,33 suggesting that circulating MK fragments and proplatelets may be processed into platelets when passing through the lung capillaries, where they are exposed to high shear rates. Shear rates conditions used in this study appear relevant to the pulmonary microcirculation, which has been suggested to be a site of platelet production.…”
mentioning
confidence: 99%